Vaccination with the Leishmania major ribosomal proteins plus CpG oligodeoxynucleotides induces protection against experimental cutaneous leishmaniasis in mice - Iborra, Salvador (2008)
Instituto de Salud Carlos III. Centro Nacional de Microbiología. Unidad de Inmunología Viral. Majadahonda, Madrid, Spain